Hubungan Antara Neutrophil Lymphocyte Ratio dan HCV RNA pada Pasien Hepatitis C Menjalani Hemodialisis yang Mendapatkan Terapi DAA di RSMH Palembang - Lilis Khairani; Suyata Suyata; Novadian Novadian; Taufik Indra Jaya (Malahayati Nursing Journal, 2023)
ABSTRACT Hepatitis C is an inflamamatory disease of the liver caused by Hepatitis C Virus (HCV) infection. Inflammatory markers are quite large in assessing the course of an infectious or inflammatory disease, one of which is the Neutrophil Lymphocyte Ratio (NLR) and the Total Viral Load of HCV RNA which combine neutrophils as active inflammatory components and lymphocytes as regulatory and protective components in a single parameter. Research on the relationship between NLR and HCV RNA in Hepatitis C outpatients undergoing hemodialysis is still limited. Therefore, this study was conducted to determine the relationship between NLR and HCV RNA in Hepatitis C patients undergoing hemodialysis who received DAA therapy who went to the outpatient clinic at Mohammad Hoesin Hospital, Palembang. Observational analytic study with a cross-sectional design with 35 Hepatitis C patients undergoing hemodialysis as subjects who were treated at the outpatient polyclinic at Mohammad Hoesin Hospital Palembang in August – November 2022. Data were obtained by recording from medical records. The data is on a categorical scale and tested using the Sperman correlation method using the SPSS version 22 application. The average NLR of Hepatitis C patients undergoing hemodialysis who had not received DAA therapy at RSMH Palembang with a high HCV RNA viral load and high NLR was 17 (12.6%) and those with low viral load and high NLR were 4 (8.4%). In addition, it is also known that the average NLR of Hepatitis C patients undergoing hemodialysis who received DAA therapy for 12 weeks at RSMH Palembang whose HCV RNA Viral Load was undetectable and the NLR was normal was 24 (24.9%) and the Viral Load was still detectable and the NLR was normal was 6 ( 5.1%). The results of the analysis showed a p value = 0.000 with a value of r = 0.738 for the relationship between NLR and HCV RNA values in patients who had not started DAA therapy and the results of the analysis showed a p value = 0.005 with a value of r = 0.50 for the relationship between NLR and HCV RNA values in patients who have received DAA therapy for 12 weeks to correlate NLR and HCV RNA values in Hepatitis C patients undergoing hemodialysis. This study showed that there was a moderately significant relationship between NLR and HCV RNA values in Hepatitis C patients undergoing hemodialysis who received DAA therapy at Mohammad Hoesin Hospital, Palembang. Keywords: Hepatitis C, Hemodialysis,  NLR, HCV RNA                                          ABSTRAK Hepatitits C adalah  penyakit inflamasi pada hati yang disebabkan infeksi Virus Hepatitis C (HCV). penanda inflamasi cukup besar dalam menilai perjalanan penyakit infeksi atau inflamasi, salah satunya Neutrophil Lymphocyte Ratio (NLR) dan Jumlah Viral Load HCV RNA yang menggabungkan neutrofil sebagai komponen inflamasi aktif serta limfosit sebagai regulator dan komponen protektif dalam satu kesatuan parameter. Penelitian mengenai hubungan antara NLR dan HCV RNA pasien rawat jalan Hepatitis C yang menjalani hemodialisis masih terbatas. Oleh karena itu, penelitian ini dilakukan untuk mengetahui hubungan antara NLR dan HCV RNA pada pasien Hepatitis C yang menjalani hemodialisis yang mendapat terapi DAA yang berobat ke poli rawat jalan di RS Mohammad Hoesin Palembang. Penelitian observasional analitik dengan desain Crossectional dengan subjek sebanyak 35 orang pasien Hepatitis C yang menjalani hemodialisis yang berobat di poli rawat jalan jalan di RS Mohammad Hoesin Palembang pada bulan Agustus - November 2022. Data diperoleh melalui pencatatan dari rekam medis. Data berskala kategorik dan diuji dengan metode korelasi spearman menggunakan aplikasi SPSS versi 22. Didapatkan Rerata NLR pasien Hepatitis C yang menjalani hemodialysis yang belum mendapat terapi DAA di RSMH Palembang yang Viral Load HCV RNA tinggi dan NLR tinggi adalah 17 (12.6%) dan yang Viral Load rendah serta NLR tinggi adalah 4 (8.4%). Selain itu juga diketahui rerata NLR pasien Hepatitis C yang menjalani hemodialysis yang mendapat terapi DAA 12 minggu di RSMH Palembang yang yang Viral Load HCV RNA tidak terdeteksi dan NLR normal adalah 24 (24.9%) dan yang Viral Load masih terdeteksi serta NLR normal adalah 6 (5.1%).  Hasil analisis menunjukkan nilai p = 0,000 dengan nilai r = 0,738 untuk hubungan antara nilai NLR dan HCV RNA pada pasien yang belum memulai terapi DAA dan Hasil analisis nilai p = 0,005 dengan nilai r = 0,50 untuk hubungan antara nilai NLR dan HCV RNA pada pasien yang sudah mendapat terapi DAA 12 minggu untuk menghubungkan antara nilai NLR dan HCV RNA pada pasien Hepatitis C yang menjalani hemodialysis. Penelitian ini menunjukan terdapat hubungan bermakna hubungan sedang antara nilai NLR dan HCV RNA pada pasien Hepatitis C yang menjalani hemodialisis yang mendapat terapi DAA di RS Mohammad Hoesin Palembang Kata Kunci: Hepatitis C, Hemodialysis, NLR; HCV RNA